Global megatrends : seven patterns of change shaping our future - Hajkowicz, Stefan; Hajkowicz, Stefan; CSIRO (Clayton South, VIC : CSIRO Publishing, 2015)
Annotation. Global Megatrends tells a story about how the world will change over the next 20 years. "Megatrends" are gradual yet powerful trajectories of change that have the potential to throw companies, individuals and societies into freefall. In Global Megatrends, author Stefan Hajkowicz identifies seven patterns of global change: resource scarcity; the challenge to protect biodiversity and the global climate; the world's ageing demographic; digital technology transformation; rapid economic growth and urbanization in the developing world; societal and consumer expectation for experiential goods and services; and finally a world where human innovation makes (just about) anything possible. This book captures the thinking of many dedicated scientists and researchers who have devoted their careers to exploring and understanding change. The change heralded by megatrends lies beyond our direct control but not beyond our influence. By getting a picture of how the world is changing and what these megatrends are, we can alter our destiny.
1. Introduction -- 2. Thinking about the future -- 3. A history of the future -- 4. A moment of serendipity (and seven megatrends) -- 5. More from less -- 6. Going, going...gone? -- 7. The Silk Highway -- 8. Forever young -- 9. Virtually here -- 10. Great expectations -- 11. The innovation imperative -- 12. Falling and landing -- 13. Conclusion -- References -- Index.
Includes bibliographical references (pages 183-197) and index.
Keywords: Social prediction; Twenty-first century -- Forecasts; Change; Sustainable living; Technological innovations; Demographic transition; Change; Demographic transition; Social prediction; Sustainable living; Technological innovations; Twenty-first century; Australian; Forecasts